2022
DOI: 10.1111/psyg.12829
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and psychological symptoms of early‐onset and late‐onset Alzheimer's disease among Chinese adults: analysis of modifiable factors

Abstract: Background To conduct a comprehensive comparison of behavioural and psychological symptoms of dementia (BPSD) in Chinese people with early‐onset Alzheimer's disease (EOAD) and late‐onset Alzheimer's disease (LOAD) and analyse the factors of differences. Methods A cross‐sectional survey of 93 EOAD and100 LOAD and their caregivers in China from November 2018 to May 2019. Results The total Neuropsychiatric Inventory score was significantly higher in LOAD. A higher level of agitation in EOAD was related to a lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…However, previous literature reported there were no gender differences concerning irritability or agitation among people with AD, 16 and people with EO‐AD were less agitated than people with late‐onset AD 17 . These contrasting results may be explained by the fact that the emotional relationship between people with dementia and caregivers is influenced by caregivers' attitudes and quality of life 18 . As shown in Table 1, spouses were more likely to notice anomalies, and as many respondents in this study were spouses, spouses' subjectivity might have influenced our results.…”
Section: Discussionmentioning
confidence: 80%
“…However, previous literature reported there were no gender differences concerning irritability or agitation among people with AD, 16 and people with EO‐AD were less agitated than people with late‐onset AD 17 . These contrasting results may be explained by the fact that the emotional relationship between people with dementia and caregivers is influenced by caregivers' attitudes and quality of life 18 . As shown in Table 1, spouses were more likely to notice anomalies, and as many respondents in this study were spouses, spouses' subjectivity might have influenced our results.…”
Section: Discussionmentioning
confidence: 80%
“…1 Additionally, the authors showed that an improvement in BPSD was associated with positive attitudes and fewer expressions of criticism. 1 We agree that positive aspects of caregiving are important. However, previous longitudinal studies have reported that BPSD impacts caregiver burden.…”
mentioning
confidence: 89%
“…The authors reported significant differences in BPSD between the EOAD and LOAD groups at baseline. 1 We would like to discuss their result in detail below.Fang et al reported that worse caregiver attitudes were associated with more severe overall psychobehavioural symptoms in the EOAD group. 1 Additionally, the authors showed that an improvement in BPSD was associated with positive attitudes and fewer expressions of criticism.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of carer burden, psychological distress and quality of life have been described for the care-partners who are often the spouses of individuals with dementia [58–60]. The behaviour changes associated with dementia are a significant cause of adverse mental health for caregivers, though it remains unclear whether these behaviours seen in YOD compared to OOD are more frequent or more severe or cause more distress for their respective caregivers [61–63,64 ▪▪ ]. In FTD, apathy, disinhibition and psychosis were strongly associated with caregiver burden [65 ▪ ] with more frequently problem-focused and positive emotion coping strategies employed by their caregivers [66].…”
Section: Psychosocialmentioning
confidence: 99%